1978
DOI: 10.1002/j.2050-0416.1978.tb03836.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Basic Compounds Derived From Roasted Barley

Abstract: By gas chromatography/mass spectrometry twenty-three basic heterocyclic compounds have been identified in an extract from roasted barley. Several other such compounds have been identi fied tentatively. The classes of compounds include pyridines, pyrazines, thiazoles and oxazoles. Such compounds appear to contribute to the flavour of beer brewed with grists containing roasted barley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Collin et al (1971) and Harding et al (1978) reported that methyl pyrazine, and 2,6-dimethyl pyrazine were the important pyrazine compounds in roasted barley. The 2-furancarboxaldehyde was significantly higher in roasted malt and methyl pyrazine was significantly higher in roasted barley than in the other samples.…”
Section: Flavor Compounds Of Roasted Malt Extract Roasted Barley Extmentioning
confidence: 99%
“…Collin et al (1971) and Harding et al (1978) reported that methyl pyrazine, and 2,6-dimethyl pyrazine were the important pyrazine compounds in roasted barley. The 2-furancarboxaldehyde was significantly higher in roasted malt and methyl pyrazine was significantly higher in roasted barley than in the other samples.…”
Section: Flavor Compounds Of Roasted Malt Extract Roasted Barley Extmentioning
confidence: 99%
“…A range of volatile pyrazine‐containing molecules were reported in roasted barley by Collins , Harding et al . and Wang et al . .…”
Section: Resultsmentioning
confidence: 91%
“…A range of volatile pyrazine-containing molecules were reported in roasted barley by Collins (17), Harding et al (18) and Wang et al (19). Yahya et al (20) also focused on the impact of roasting processes on flavour though not on functional properties.…”
Section: Studies With Hot Water Extractsmentioning
confidence: 99%
“…Efficient techniques are necessary for investigating such nitrogen heterocycles usually found at very low concentration. The literature is poor in this field, and different authors report measured concentrations differing in order of magnitude from ppm (parts of compounds per 10 6 parts of water) to sub-ppb (parts of compounds per 10 9 parts of water) for the same food (Harding et al, 1978;Qureshi et al, 1979a,b;Narziss et al, 1986Narziss et al, , 1988Narziss et al, , 1989). Such differences could not be due to intrinsic variability of the material.…”
Section: Introductionmentioning
confidence: 99%